Evaluasi Program Hammalatul Qur’an dalam Meningkatkan Bacaan dan Hafalan Al Qur’an Guru - Yurika, Tince Ajeng; Warlizasusi, Jumira; sumarto, Sumarto (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
This study aimed to describe the evaluation of the Hammalatul Qur'an Program at SDIT Rabbi Radhiyya 02 Rejang Lebong in improving teachers’ reading and memorization of the Qur'an. To know the achievement level of the goal had been set, an evaluation was needed related to its management functions, planning, implementation, checking/evaluation and corrective action activities on the implementation of the program. In its implementation, the Plan Do Check and Act (PDCA) approach was applied. This study aimed to determine the extent to which teachers have mastered and achieved the objectives of the program. The information obtained from the evaluation using the PDCA model became the feedback to the implementation of the program and itwould be used to improve the Hammalatul Qur'an program in the future. This research method employed a descriptive qualitative approach, in which the data were collected through observation and interviews to the Hammalatul Qur'an team, and supported by some related literature. The research data were reduced and presented, then analyzed for several conclusions. The results showed that planning (Plan) stage createdthree formulation products, namelyvision, mission and objectives of the program. Implementation (Do) stage was in the forms of regular training. Evaluation (Check) stage was done byhaving initial tests and final tests for the program. The follow-up (Act) stage was by issuing a report card ofHammalatul Qur'an and the coaching session.